2016
DOI: 10.1080/09168451.2016.1171697
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of myricetin from Diospyros lotus through suppression of NF-κB and STAT1 activation and Nrf2-mediated HO-1 induction in lipopolysaccharide-stimulated RAW264.7 macrophages

Abstract: Diospyros lotus is traditionally used for the treatment of diabetes, diarrhea, tumor, and hypertension. The purpose of this study was to investigate the anti-inflammatory effect and underlying molecular mechanisms of myricetin in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Myricetin dose-dependently suppressed the production of pro-inflammatory mediators (NO, iNOS, PGE2, and COX-2) in LPS-stimulated RAW264.7 macrophages. Myricetin administration decreased the production of NO, iNOS, TNF-α, IL-6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 37 publications
6
46
0
1
Order By: Relevance
“…Further investigation revealed that the activity of NF- κ B was much higher in Nrf2 −/− mice than in their wild-type counterparts [21]. In LPS-stimulated RAW264.7 macrophages, M treatment suppressed the production of NO, iNOS, TNF- α , IL-6, and IL-12 by depressing the activity of NF- κ B and the degradation of I κ B- α via promoting Nrf2/HO-1 pathway [22]. Our study indicated that silencing of Nrf2 could further activate the phosphorylation of I κ B- α /NF- κ B/p65 signaling in NRCM after incubation with high glucose for 72 h. We also detected further overexpression of IL-1 β , IL-6, and TNF- α at mRNA level after Nrf2 silencing by stimulating with LPS for 16 h. These results were coincident with previous reports that Nrf2 could inhibit I κ B- α /NF- κ B/p65 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed that the activity of NF- κ B was much higher in Nrf2 −/− mice than in their wild-type counterparts [21]. In LPS-stimulated RAW264.7 macrophages, M treatment suppressed the production of NO, iNOS, TNF- α , IL-6, and IL-12 by depressing the activity of NF- κ B and the degradation of I κ B- α via promoting Nrf2/HO-1 pathway [22]. Our study indicated that silencing of Nrf2 could further activate the phosphorylation of I κ B- α /NF- κ B/p65 signaling in NRCM after incubation with high glucose for 72 h. We also detected further overexpression of IL-1 β , IL-6, and TNF- α at mRNA level after Nrf2 silencing by stimulating with LPS for 16 h. These results were coincident with previous reports that Nrf2 could inhibit I κ B- α /NF- κ B/p65 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, myricetin has been showed to protect the mouse or rat heart from isoproterenol induced myocardial infarction(Tiwari, Mohan, Kasture, Maxia, & Ballero, ), ischemia/reperfusion induced injury (Scarabelli et al, ), and hypertension (Borde, Mohan, & Kasture, ), and the underlying mechanism was related to the regulation of Stat1 and oxidative stress (Borde et al, ; Scarabelli et al, ; Tiwari et al, ). In in vitro experiments, myricetin could blunt the activation of NF‐κB and inhibit the production of proinflammatory cytokines in H9C2 cardiomyocytes (Chen & Fan, ) and macrophages (Cho et al, ). Our data confirmed the role of myricetin in antagonizing LPS induced inflammatory response in NRCM and macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…In H9c2 cardiomyocytes, myricetin mitigated the inflammatory responses induced by LPS through regulation of oxidative stress and IκB/NFκB (p65) signaling pathway (Chen & Fan, ). In macrophage, myricetin inhibited the production of inflammatory cytokines by suppressing the activity of NFκB and STAT1 (Cho et al, ). These in vitro experiments have implied the potential benefits of myricetin in SIMD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Morin treatment prior to H 2 O 2 exposure significantly prevented the generation of ROS, increased cell viability and prevented DNA damage by up-regulating Nrf2-dependent HO-1 expression through extracellular signal-regulated kinases (ERK) in C2C12 myoblasts [133]. In the case of myricetin, production of pro-inflammatory mediators through the suppression of signal transducer and activator of transcription 1 (STAT1) and Nuclear factor kappa-lightchain-enhancer of B cells (NF-kB) activation was inhibited by induction of Nrf2-mediated HO-1 expression in LPS-stimulated macrophages [134].…”
Section: Modulation Of Nrf2 Activity By Phenolic Compoundsmentioning
confidence: 99%